Morphological Evaluation of the Production Parameters of Cowpea Varieties (Vigna unguiculata) Grown in Maniema (D.R. Congo) - MWISSA MUSOKE, Venant; MOKE LUKUSA, Bopole; BONONGA OKANI, Juré; ALIANGO UVON, Blaise; PALUKU NZIABAKI, Augustin; NGAMA BOLOY, Faustin; DHED’A DJAILO, Benoit; YENGA BOMBEKU, Dimanche (European Journal of Science, Innovation and Technology, 2026)
Cowpea (Vigna unguiculata [L.] Walp.) is a major dietary legume contributing to food security in Africa. In Maniema, Democratic Republic of Congo, data on the productive diversity of local cowpea accessions remain limited. This study aimed to evaluate this diversity of cowpea cultivated in this Province on the basis of a few production parameters. An experimental test was conducted according to an appropriate set-up and accessions were evaluated according to a number of production parameters. The data were subjected to an analysis of variance (ANOVA), supplemented by the calculation of coefficients of variation and the analysis of correlations between traits. The results revealed significant differences (p < 0.05) between accessions for the majority of the parameters studied, reflecting an exploitable productive variability. Significant positive correlations were observed between the number of pods per plant, the number of seeds per pod, and seed yield. Some accessions have been distinguished by superior performance, indicating interesting agronomic potential and good adaptation to local agro-ecological conditions. This diversity is a strategic resource for varietal selection and the sustainable improvement of cowpea production in Maniema.